EVALUASI PROGRAM SISTEM PENDIDIKAN TERPADU DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN ACEH BESAR (Evaluating the Program of Integrated Education System of the Department of Education and Culture, Aceh Besar District) - silahuddin silahuddin; Ana Sofia (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2021)
This study aims to determine the achievements of the Integrated Education Program implemented by the Department of Education in Aceh Besar. The implementation of this program is motivated by various conditions that occur in Aceh Besar, such as there are still many cases related to community morals, both at the level of children and adults, so that shaping the character of the community through schools is crucial. Among the efforts made by the Department of Education in Aceh Besar is to implement Integrated Education at schools. The results of the research found that the implementation of the Integrated Education Program had taken place in accordance with the stages and standards that had been set. Furthermore, it is hoped that an integrated education system process will be carried out in each target school and there will be an increase in the quality of education to create the students with Islamic characteristics. This program is expected to be a model that can be adopted by other local governments, in order to achieve national education goals, both local and national levels.